The Cambridge illustrated history of China - Ebrey, Patricia Buckley 1947- (Cambridge University Press, 2023)
<<The>> Cambridge Illustrated History of China is an illuminating account of the full sweep of Chinese civilisation - from prehistoric times to the intellectual ferment of the Warring States Period, through the rise and fall of the imperial dynasties, to the modern communist state. Written by a leading scholar and lavishly illustrated, its narrative draws together everything from the influence of key intellectual figures, to political innovations, art and material culture, family and religious life, not to mention wars and modern conflicts. This third revised edition includes new archaeological discoveries and gives fuller treatment of environmental history and Chinese interaction with the wider world, placing China in global context. The Qing dynasty is now covered in two chapters, while the final chapter brings the story into the twenty-first century, covering the transformation of China into one of the world's leading economies and the challenges it faces. Lively and highly visual, this book will be appreciated by anyone interested in Chinese history.
Keywords: Geschichte; China